What is the product?

(negative 3 s + 2 t)(4 s minus t)

negative 12 s squared minus 2 t squared
negative 12 s squared + 2 t squared
negative 12 s squared + 8 s t minus 2 t squared
negative 12 s squared + 11 s t minus 2 t squared

Respuesta :

Answer:

[tex] \boxed{- 12 {s}^{2} + 11st - 2 {t}^{2} } [/tex]

Step-by-step explanation:

[tex] = > ( - 3s + 2t)(4s - t) \\ \\ = > - 3s(4s - t) + 2t(4s - t) \\ \\ = > ( ( - 3s) \times 4s )- (( - 3s) \times t) + (2t \times 4s) - (2t \times t) \\ \\ = > - 12 {s}^{2} - ( - 3st) + 8st - 2 {t}^{2} \\ \\ = > -12 {s}^{2} + 3st + 8st - 2 {t}^{2} \\ \\ = > - 12 {s}^{2} + 11st - 2 {t}^{2} [/tex]